Blue dye is sufficient for sentinel lymph node biopsy in breast cancer. Issue 4 (3rd February 2014) - Ang, C. H.; Tan, M. Y.; Teo, C.; Seah, D. W.; Chen, J. C.; Chan, M. Y. P.; Tan, E. Y.
<x xml:space="preserve">Abstract</x> Background Most previous studies have reported superior results when blue dye and radiocolloids were used together for sentinel lymph node (SLN) biopsy in early breast cancer. Blue dye was reported to perform poorly when used alone, although more recent studies have found otherwise. This study reviewed the authors' practice of performing SLN biopsy with blue dye alone. Methods This was a retrospective review of patients who underwent SLN biopsy using blue dye alone from 2001 to 2005, when SLN biopsy was performed selectively and always followed by axillary lymph node dissection (ALND), and from 2006 to 2010, when SLN biopsy was offered to all suitable patients and ALND done only when the SLN was not identified or positive for metastasis. Results Between 2001 and 2005, 170 patients underwent SLN biopsy with blue dye alone. The overall SLN non‐identification rate was 8·4 per cent. The overall false‐negative rate was 34 per cent, but decreased with each subsequent year to 13 per cent in 2005. From 2006 to 2010, 610 patients underwent SLN biopsy with blue dye alone. The SLN was not identified in 12 patients (2·0 per cent) and no significant contributing factor was identified. A median of 2 (range 1–11) SLNs were identified. A non‐SLN was found to be positive for metastasis in two patients with negative SLNs. Axillary nodal recurrence developed in one patient; none developed internal mammary nodal recurrence. Anaphylaxis occurred in one patient. Conclusion Blue dye performed well as a single modality for SLN biopsy. Non‐identification, axillary nodal recurrence and serious allergic reactions were uncommon.